The Social Interaction Process of Former Drug Addicts in The Post-Rehabilitation Community - Ilyas (International Journal of Education and Humanities, 2023)
Cases related to drug use continue to occur. Narcotics are often seen as a solution to the life problems faced by addicts. In fact, drugs will actually add new problems to life. Drug users for themselves are considered victims and therefore do not need to serve a prison term but must undergo a rehabilitation process. The problem is not over yet because after undergoing a period of rehabilitation, former drug addicts will face a society that considers them as the scum of the society so that they have the potential to experience discrimination, gossip and also expulsion. Therefore, it is important to see how the social interaction process of former drug addicts after completing the rehabilitation period. The method used in this research is descriptive with a qualitative approach. The subjects of this research are former drug addicts who have undergone a rehabilitation period with five informants. The results showed that former drug addicts had a difficult time returning to society. The existence of shame, fear, and also stigma from society makes them need time to adapt. So, there needs to be support from family, friends, neighbours, and also their environment to provide social support so that they do not fall back into the influence of drugs. Society also needs to remove the negative stigma on drug addicts for themselves because drug users, dealers and dealers are different things